Effects of corporate brand image on sustainability of National Health Insurance in Ghana (case study of Sekyere East District) - Agyemang, Patrick (2016)
A thesis submitted to the Department of Marketing and Corporate Strategy, College of Humanities and Social Science in partial fulfillment of the requirements for the degree of Master of Business Administration